A spatial approach to improve coastal bioregion management of the north western Australia - Kordi, Moataz Nael S; O'Leary, Mick (Pergamon, 2016)
Coral reefs are a major coastal feature of the Kimberley bioregion in north-western Australia; however, very little is known about the habitats and substrates of the reefs in this coast. Previous studies have been conducted on a broad scale, but no geomorphological, surface substrate and habitat maps of the reefs have been produced. Such maps would provide researchers and coastal zone managers with significant information and estimations of reef growth and productivity. The primary aim of this study was to obtain detailed information on reefs in the Kimberley bioregion. This study used remote sensing and Geographic Information Systems (GIS), as well as multiple other data sources, to map reef geomorphic zones and the associated key habitats and substrate types of shallow nearshore reefs. Despite the macrotidal regimes and the turbid waters of the study area, remote sensing was effectively used to identify the dominant habitats and substrate types of eight reef platforms. This study provides long-term quantitative assessments of the main habitats and substrates of these reefs and offers a better understanding of reefs in the Kimberly bioregion. It is also a source of valuable information for the marine park and coastal managers investigating the coral reefs that have been targeted for conservation, but have not yet been the subject of regional analysis.